Round temples in Roman architecture of the Republic through the late Imperial period - Armstrong, N (2001)
Roman round temples are usually discussed either in the context of round buildings like baths and mausolea or on a case-by-case basis. Both approaches fail to reveal what makes round temples a distinct architectural type and moreover, what reasons can account for their use throughout the Roman world. By examining round temples from the Republic, when they are first attested, to the early fourth century AD, this thesis aims to explain why the round form had such a lasting appeal. It follows a chronological approach, discussing the evidence for individual temples and situating them within their historical, social, topographical, and architectural contexts. In a comparative analysis, the building components, materials, techniques, decorative details, and proportions employed by round temples are outlined to reveal influences on their design. The round temples discussed in this study are concentrated in Italy, Greece, and Asia Minor. While the earliest examples in Rome draw on Italic traditions, from the late Republic, round temples begin to reflect Greek trends. Greek tholoi and the Greek decorative repertory, balanced by Roman developments in design, have a lasting influence on round temples. Based on tholoi, scholars have assumed that Roman round temples honored Vesta and divinized heroes. While they were celebrated with a few examples, the majority were dedicated to other gods and goddesses. As a result, religious, social, topographical and aesthetic reasons are proposed to explain the enduring appeal of round temples. Like the motivations behind their foundations, the plans, dimensions, and proportional relationships employed by round temples are noted for their diversity. For their individuality and inventive spirit, round temples make a significant contribution to the Roman architectural repertory.